The ameliorative effect of Lactobacillus plantarum Y44 oral administration on inflammation and lipid metabolism in obese mice fed with a high fat diet. Issue 6 (12th June 2020) - Liu, Yujun; Gao, Yuan; Ma, Fenglian; Sun, Mengying; Mu, Guangqing; Tuo, Yanfeng
Abstract : In our previous studies, Lactobacillus plantarum Y44 showed antioxidant activity and favorable gastric and intestinal transit tolerance. Abstract : In our previous studies, Lactobacillus plantarum Y44 showed antioxidant activity and favorable gastric and intestinal transit tolerance. The purpose of this study is to determine whether L. plantarum Y44 could ameliorate intestinal inflammation and lipid metabolism disorder in obese mice fed with a high-fat diet. L. plantarum Y44 was administered by gavage to the mice fed with a high-fat diet for 12 weeks. The mice fed with a high fat diet only showed sustainably elevated body weight, liver lipid metabolism disorder, intestinal inflammation and a lower short chain fatty acid content in feces. Oral administration of L. plantarum Y44 regulated lipid metabolism disorder by inhibiting the expression of fatty acid synthase (FAS) and acetyl-CoA carboxylase (ACC) in the liver of obese mice, reducing the contents of total cholesterol (TC), triacylglycerols (TG), low density lipoprotein cholesterol (LDL-c), alanine aminotransferase (ALT), and aspartate transaminase (AST) and increasing the content of high-density lipoprotein cholesterol (HDL-c) in the serum of obese mice. Oral administration of L. plantarum Y44 up-regulated the expression of colon tight junction protein such as claudin-1 and occludin, down-regulated p38 and phospho-p38 levels and reduced serum interleukin-8 (IL-8) and tumor necrosis factor-α (TNF-α). Oral administration of L. plantarum Y44 increased Muribaculaceae, Rikenellaceae, and Lactobacillaceae levels, reduced the Firmicutes / Bacteroidetes ratio, and Desulfovibrionaceae and Proteobacteria levels in obese mice. Oral administration of L. plantarum Y44 also enhanced the contents of propionic acid, butyric acid, butanoicacid-3-methyl, pentanoic acid and acetic acid in the feces of the obese mice. Correlation analysis of Spearman revealed a significant correlation between changes in intestinal microflora and obesity-related symptoms. L. plantarum Y44 ameliorated intestinal inflammation and lipid metabolism disorders by modulating gut microbiota.